An updated review of the salient geomedical aspects of mercury for enhancement of data quality in simulation modelling and other prognostic applications: Africa case descriptions - Davies, Theophilus C. (Frontiers in Analytical Science, 2023)
Improved input data quality for application of simulation modelling techniques in understanding the dynamics of mercury toxicity: With Africa case descriptions Theophilus C. Davies Faculty of Natural Sciences, Mangosuthu University of Technology, 511 Mangosuthu Highway, KwaZulu Natal, Republic of South Africa – email: theo.clavellpr3@gmail.com; daviestheophilus@mut.ac.za ORCID: https://orcid.org/0000-0002-8299-1121 ABSTRACT Mercury (Hg) pollution is a global problem. Despite the prolificity of research in the past two decades or so, there are still several uncertainties and variabilities in our knowledge of both the element’s exposure dynamics and its health effects. Understanding the intricacies of the element’s emissions-to-impact path, for instance, is rendered intractable by its varied environmental fate and the overarching influence of environmental, geochemical, biological and socioeconomic drivers. A thorough knowledge of the geomedical characteristics of Hg and the inclusion of their most refined and updated analogues as part of the input data in Hg simulation modelling experiments, is important, for this reflects strongly on the accuracy of model output. As a contribution towards eliminating or reducing these knowledge gaps, this paper presents a brief and updated overview of the relevant and more important geomedical characteristics of Hg, as part of the provision of high-quality input data needed in Hg simulation modelling studies. This would enable the production of model outcomes accurate enough for application in obviating some of the knowledge gaps, such as the capacity to design better exposure-limiting strategies; and how the course of diagnosis and treatment currently proffered by physicians for Hg-induced maladies, can be revised or expanded. Model results derived from high-quality input datasets also have a high potential for providing forecasting capabilities to inform policy. Keywords: Mercury; uncertainties; geomedical characteristics; exposure; input data quality; simulation analysis; model validation; addressing the issues simulation modelling